Pantun Sebagai Bentuk Komunikasi Lingkungan Masyarakat Uluan di Sumatera Selatan - Yenrizal, Yenrizal; Muhaimin, Ahmad; Sirozi, Muhammad (Jurnal Komunikasi, 2024)
The purpose of this study was to find and explain the existence of pantun as a means of environmental communication in the Uluan community of South Sumatra. The study used a qualitative method. Data were collected through in-depth interviews, observations, and searches for relevant documents. The results of this study indicate that environmental communication in pantun can be divided into two categories. The first category explicitly refers to environmental issues, and the second category is not explicitly related to environmental issues, but its implicit meaning refers to environmental issues. This study also found that pantun as a form of environmental communication in the Uluan community of South Sumatra is dynamic and continues to reproduce. Because pantun is rooted and sourced from the environmental conditions of the community itself, this study recommends that pantun can be a medium for environmental campaigns.